Bending fracture rule for 3D-printed curved continuous-fiber composite. (4th July 2019) - Ishii, Kouki; Todoroki, Akira; Mizutani, Yoshihiro; Suzuki, Yoshiro; Koga, Yoichiro; Matsuzaki, Ryosuke; Ueda, Masahito; Hirano, Yoshiyasu
Abstract : Three-dimensional (3D) printing is an attractive technology to produce complex structures without the need for expensive tools and molds. Additives are usually incorporated with the plastic materials used in 3D printing to increase their strength and rigidity. In particular, carbon fiber-reinforced plastic (CFRP) shows promise as a material for use in 3D printing. However, the strength of CFRP after printing is still unclear, although it is known that its strength is affected by the plastic melting during printing. In this study, we analyzed the fracture behavior of CFRP specimens before and after bending to different curvature radii. From the experimental results, a fracture criterion that described the behavior of the materials by considering tensile and compressive loads was developed. The fracture mechanism was the same for CFRP specimens with different curvature radii. These results increase our understanding of the mechanical properties of CFRP materials used in 3D printing.